The Movement for the Abolition of Child Labour as an Example of a Transnational Network Movement. (1st April 2008) - Patrick Develtere; An Huybrechs
Abstract : With the advent of a global network society, movements and social organisations acquire a new place and space in development. A wide range of actors, including international nongovernmental organisations and transnational coalitions, are reacting in a variety of ways to new domestic and global challenges. Separated from traditional social movements, such as trade unions, new forms of collective action have emerged on the international scene which can be described as 'transnational network movements'. This paper discusses the differences in ideology, practice, and organisation between traditional social movements and these new network movements, using the movement for the abolition of child labour as an example. The history of this movement, the actors involved and its repertoire of actions illustrate clearly that transnational network movements are very dynamic and open environments in which a wide variety of national and international organisations and movements, as well as institutions, corporations and individuals, can choose their own level of involvement whilst managing to develop a certain social power.